Focal cerebral ischemia induces the neurogenic potential of mouse Dach1-expressing cells in the dorsal part of the lateral ventricles - Honsa, P; Pivonkova, H; Anderova, M (Neuroscience, 2013)
The mouse Dach1 gene, involved in the development of the neocortex and the hippocampus, is expressed by neural stem cells (NSCs) during early neurogenesis, and its expression also continues in a subpopulation of cells in the dorsal part of the lateral ventricles (LV) of the adult mouse brain. In this study we aimed to elucidate the role of Dach1-expressing cells in adult neurogenesis/gliogenesis under physiological as well as post-ischemic conditions, employing transgenic mice in which the expression of green fluorescent protein (GFP) is controlled by the D6 promotor of the mouse Dach1 gene. A neurosphere-forming assay of GFP⁺ cells isolated from the dorsal part of the LV was carried out with subsequent differentiation in vitro. To elucidate the neurogenic/gliogenic potential of GFP⁺ cells in the dorsal part of the LV, in situ immunohistochemical/electrophysiological analyses of GFP⁺ cells in adult sham-operated brains (controls) and those after middle cerebral artery occlusion (MCAo) were performed. The GFP⁺ cells isolated from the dorsal part of the LV of controls formed neurospheres and differentiated solely into a glial phenotype, while those isolated after MCAo also gave rise to cells with the properties of neuronal precursors. In situ analyses revealed that GFP⁺ cells express the phenotype of adult NSCs or neuroblasts in controls as well as following ischemia. Following MCAo we found a significantly increased number of GFP⁺ cells expressing doublecortin as well as a number of GFP⁺ cells migrating through the rostral migratory stream into the olfactory bulb, where they probably differentiated into calretinin⁺ interneurons. Collectively, our results suggest the involvement of the mouse Dach1 gene in adult neurogenesis; cells expressing this gene exhibit the properties of adult NSCs or neuroblasts and respond to MCAo by enhanced neurogenesis.
Keywords: buněčná diferenciace; Tetrodotoxin; 4-aminopyridin; proteiny nervové tkáně; Sodium Channel Blockers; techniky in vitro; zelené fluorescenční proteiny; dospělé kmenové buňky; Mice, Transgenic; Nerve Tissue Proteins; Neurogenesis; Green Fluorescent Proteins; myši transgenní; Patch-Clamp Techniques; počet buněk; zvířata; ventriculi laterales; neurony; myši; metoda terčíkového zámku; myši inbrední C57BL; 4-Aminopyridine; Mice; tetrodotoxin; tetraethylamonium; blokátory sodíkových kanálů; degenerace nervu; infarkt arteria cerebri media; oční proteiny; Cell Differentiation; Eye Proteins; Infarction, Middle Cerebral Artery; Mice, Inbred C57BL; Neurons; Tetraethylammonium; In Vitro Techniques; Lateral Ventricles; Adult Stem Cells; Animals; Membrane Potentials; membránové potenciály; Disease Models, Animal; Cell Count; Nerve Degeneration; neurogeneze; modely nemocí na zvířatech